2007
DOI: 10.1111/j.1530-0277.2007.00505.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association of Alcohol Dependence and Habitual Smoking With Catechol‐O‐methyltransferase

Abstract: Objective: To test whether variation in the gene encoding the enzyme catechol-O-methyltransferase (COMT), which catalyzes the breakdown of dopamine and other catecholamine neurotransmitters, is associated with the risk for alcohol dependence and habitual smoking.Methods: Single nucleotide polymophisms (SNPs) were genotyped in a sample of 219 multiplex alcohol-dependent families of European American descent from the Collaborative Study on the Genetics of Alcoholism (COGA). Family-based tests of association were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 67 publications
(69 reference statements)
0
19
1
Order By: Relevance
“…Met158 has been reported to be associated with low activity of enzyme [29,44,45] and literature suggests Asian population in which risk appears to be associated with Met158 [11,29]. Studies by Foroud et al and Ishiguro et al did not find any association with AD [10,46]. We observed significant difference between Val/Met genotype between the cases and controls.…”
Section: Discussioncontrasting
confidence: 41%
See 2 more Smart Citations
“…Met158 has been reported to be associated with low activity of enzyme [29,44,45] and literature suggests Asian population in which risk appears to be associated with Met158 [11,29]. Studies by Foroud et al and Ishiguro et al did not find any association with AD [10,46]. We observed significant difference between Val/Met genotype between the cases and controls.…”
Section: Discussioncontrasting
confidence: 41%
“…Contrasting results were observed by Ishiguro et al [10] who also utilized PCR-RFLP but reported no difference in allele frequency distribution between 175 cases and 354 age and sex matched Japanese subjects. A family based association study by Foroud et al [46] indicated that presence of COMT (Val158Met) polymorphism did not affect the pathology of alcohol consumption and smoking in European-Americans. Thus, irrespective of the differences in the methodology, the contradictory findings are likely due to differences in ethnicity, type of study (case-control/ family based association study) demographic differences, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, genetic variations in the dopamine-metabolizing enzymes catechol-O-methyltransferase and monoamine oxidase A (MAOA) have been found to be associated with the risk for alcohol dependence [75,76,77], although these results could not be uniformly replicated [78,79,80]. Other studies have linked genetic variations in the dopamine transporter 1 gene to the severity of withdrawal symptoms [81,82].…”
Section: Candidate Gene Studiesmentioning
confidence: 92%
“…The available evidence from the genetic association studies published to date on the association between alcoholism and COMT 472G/A gene polymorphism have produced inconclusive or contradicted results (Enoch et al, 2006;Foroud et al, 2007). Each of these studies typically involved few cases and controls and, therefore, was neither adequate nor sufficiently informative to clearly show an association.…”
Section: Introductionmentioning
confidence: 96%